Penerapan Pendidikan Multikultural untuk Menumbuhkan Budaya Toleransi - Ricki Rianto Koho; Zainur Wula (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
This study aims to analyze the implementation of multicultural education in fostering a culture of tolerance, particularly at SMA Negeri 3 Kalabahi. The research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The research subjects consisted of teachers and students selected through purposive sampling. The findings reveal that multicultural education has been integrated into both classroom learning and school activities through habituation, extracurricular programs, and social interactions emphasizing mutual respect and appreciation of diversity. Teachers act as facilitators, mediators, and role models in instilling tolerance values. Supporting factors include a heterogeneous school environment and institutional policies promoting tolerance, while challenges include limited student understanding and external environmental influences. Therefore, multicultural education plays a significant role in fostering a culture of tolerance through a holistic approach in teaching and school culture.